Using a GIS-based framework to teach climate change in Kansas - Tabor, Lisa Kay (Kansas State University, 2016)
Scientists agree that there is ample evidence of climate change and that a significant portion of the change is anthropogenically driven. Leiserowitz et al. (2011b) asked teenagers about their understanding of the climate system and the causes of climate change. Fewer than 20% of respondents classified themselves as “very well informed” and only 27% reported that they learned “a lot” about climate change in school. However, of these teenagers, 70% expressed a desire for more climate change education. Even though the idea of human impacts on the climate system and a changing climate have been known and discussed within science education for several decades, dedicating classroom time for teaching climate change is not a common practice. Focus group discussions with science and agricultural education teachers (Pytlikzillig et al., 2013) emphasized the need for the use of locally relevant data in the classroom as a means to engage students in critical thinking activities that require them to use and draw conclusions from these data. However, most teachers do not have access to such data or a working knowledge of technological platforms from which they can have the students observe, manipulate, and analyze these data. This study used a mixed methods research design to explore the use of a GIS-based framework for teaching climate change. A two-part intervention was used: 1) teacher training, and 2) classroom implementation. Student-, teacher-, and classroom-centered data were collected to address student outcomes, teacher perceptions of GIS use in teaching climate change, and both students’ and teachers’ perceptions of challenges and successes of using GIS in the classroom. Students showed an overall positive growth in knowledge. Teachers shared a positive perception regarding the use of GIS to teach climate change, going so far as to report that they will all continue to teach climate change and use GIS in their classrooms. Successes and challenges were observed in classrooms, recognizing the benefits of student engagement and learning, as well as the challenges of using technology and supporting student needs. This exploratory research supports the premise that using a GIS-based framework to teach climate change is practical, reproducible, and effective.
Keywords: GIS; climate change education; geography education; science education; teacher professional development